Chemoprevention of LA7-Induced Mammary Tumor Growth by SM6Met, a Well-Characterized Cyclopia Extract - Oyenihi, Omolola R.; Krygsman, Annadie; Verhoog, Nicolette; de Beer, Dalene; Saayman, Michael J.; Mouton, Thys M.; Louw, Ann (Frontiers in Pharmacology, 2018)
Breast cancer is the leading cause of cancer-related deaths in women. Chemoprevention of breast cancer by using plant extracts is gaining attention. SM6Met, a well characterized extract of Cyclopia subternata with reported selective estrogen receptor subtype activity, has shown tumor suppressive effects in a chemically-induced breast cancer model in rats, which is known to be estrogen responsive. However, there is no information on the estrogen sensitivity of the relatively new orthotopic model of LA7 cell-induced mammary tumors. In the present study, the potential chemopreventative and side-effect profile of SM6Met on LA7 cell-induced tumor growth was evaluated, as was the effects of 17β-estradiol and standard-of-care (SOC) endocrine therapies, such as tamoxifen, letrozole and fulvestrant. Tumor growth was observed in the tumor-vehicle control group until day 10 post tumor induction, which declined afterwards on days 12-14. SM6Met suppressed tumor growth to the same extent as tamoxifen, while letrozole, but not fulvestrant, also showed substantial anti-tumor effects. Short-term 17β-estradiol treatment reduced tumor volume on days prior to day 10, whereas tumor promoting effects were observed during long-term treatment, which was especially evident at later time points. Marked elevation in serum markers of liver injury, which was further supported by histological evaluation, was observed in the vehicle treated tumor control, tamoxifen, letrozole and long-term 17β-estradiol treatment groups. Alterations in the lipid profiles were also observed in the 17β-estradiol treatment groups. In contrast, SM6Met did not augment the increase in serum levels of liver injury biomarkers caused by tumor induction and no effect was observed on lipid profiles. In summary, the results from the current study demonstrate the chemopreventative effect of SM6Met on mammary tumor growth, which was comparable to that of tamoxifen, without eliciting the negative side-effects observed with this SOC endocrine therapy. Furthermore, the results of this study also showed some responsiveness of LA7-induced tumors to estrogen and SOC endocrine therapies. Thus, this model may be useful in evaluating potential endocrine therapies for hormone responsive breast cancer.